1999
DOI: 10.1200/jco.1999.17.5.1488
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tamoxifen on Sexual Functioning in Patients With Breast Cancer

Abstract: Women treated with tamoxifen in the adjuvant setting experienced symptoms of sexual dysfunction. The individual contributions of chemotherapy and tamoxifen to sexual dysfunction warrant prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(64 citation statements)
references
References 23 publications
2
59
0
3
Order By: Relevance
“…Previous studies have been predominantly cross-sectional in nature [1][2][3][4][5][6], and those that have reported on temporal changes have relied mainly on retrospective recall rather than prospective data [2,3,5]. The prospective studies available to date have a baseline as- sessment several months after diagnosis and frequently after treatment [12,14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have been predominantly cross-sectional in nature [1][2][3][4][5][6], and those that have reported on temporal changes have relied mainly on retrospective recall rather than prospective data [2,3,5]. The prospective studies available to date have a baseline as- sessment several months after diagnosis and frequently after treatment [12,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Our current knowledge of the prevalence and nature of sexual dysfunction in women with breast cancer is derived mainly from cross-sectional studies [1][2][3][4][5][6], which demonstrate that 30%-60% of women treated for breast cancer report sexual problems. Specific concerns include vaginal dryness (42%-56%) [1][2][3], dyspareunia (35%-52%) [1,[3][4][5], and low libido (48%-64%) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Findings indicated no difference in sexual functioning (as measured by the CARES) between women treated with or without tamoxifen. Finally, Mortimer et al 27 assessed sexual functioning using the Sexual History Form in breast cancer survivors treated with tamoxifen for 2 to 24 months previously. Levels of sexual dysfunction for this sample were found to be comparable to those in a normative sample of healthy women.…”
Section: Relation Of Specific Forms Of Breast Cancer Treatment To Sexmentioning
confidence: 99%
“…Similarly, Ganz et al examined the relation between tamoxifen usage and sexual functioning in breast cancer survivors and they revealed no difference in sexual functioning between women treated with or (36). In contrast with these studies, Joanne et al observed that women treated with tamoxifen could experience symptoms of sexual dysfunction (19).…”
Section: Discussionmentioning
confidence: 93%
“…In a related study with limited number of patients, it is reveald that treatment with tamoxifen may not lead to contribute sexual problems (18). On the contrary, when vaginal smears were obtained before and after tamoxifen treatment, it is found that this drug has estrogen agonist effect on vaginal mucosa (19). So, treatment with tamoxifen may cause vaginal atrophy and problems with sexual desire.…”
Section: Introductionmentioning
confidence: 99%